165 ROLE OF INHIBITOR OF DIFFERENTIATION 2 (ID2) DURING MOUSE LUNG EMBRYOGENESIS. (1st January 2006) - Londhe, V. A.; Li, X.; Nguyen, H. T.; Li, C.; Zhu, N.; Li, M.; Minoo, P.
Abstract : Background: The morphoregulatory molecules that drive lung development broadly fall into three classes. These include transcription factors, signaling molecules, and extracellular matrix (ECM) proteins and receptors. The signaling molecules, bone morphogenetic protein (BMP)-4 and transforming growth factor (TGF)-β play critical functions in determining the fate of target cells via signaling pathways involving inhibitor of differentiation (Id) proteins. Id proteins are negative regulators of the basic helix-loop-helix (bHLH) family of transcription factors that act as positive regulators of cell proliferation and negative regulators of cell differentiation. There is currently little to no information regarding the role of Id2 proteins in lung morphogenesis. Objectives: To determine the role of Id2 during mouse lung embryogenesis by (1) characterizing Id2 mRNA and protein expression pattern in wild-type mice and (2) generating hypermorphic transgenic mice for Id2 to determine the phenotypic impact of Id2 overexpression. Design/Methods: Pregnant wild-type C57BL/6 mice and newborn pups were sacrificed to obtain fetal lungs at designated gestational ages ranging between E12 and E18. Adult mouse lungs were also harvested. The lungs were used for mRNA, protein, and immunohistochemical analysis of Id2. Additionally, a transgenic mouse line was generated by first subcloning human Id2 cDNA into an SpC-promoter-driven expression vector followed by subsequent injection into single- to two-staged mouse embryos and reimplantation into pseudopregnant female mice. The offspring were then genotyped to establish expression of the Id2 transgene and lungs were harvested for histological analysis. Results: Id2 mRNA expression in the developing lung increased from baseline levels at E12 to maximal at E15 through postnatal day 1 and subsequently decreased by adulthood based on RT PCR and Northern blot analysis of embryonic lung RNA extracts. In situ hybridization also showed that the spatial pattern of Id2 expression was localized to the distal tips of branching lung epithelium at E12. Immunohistochemical analysis revealed a similar pattern of Id2 protein expression at E15. Conclusions: The temporal and spatial expression of Id2 mRNA and protein in the developing mouse lung suggests that Id2 may play an important morphoregulatory role during lung embryogenesis. The molecular signaling between key signaling molecules that may regulate Id2 expression remains to be elucidated.Supported by grant 401379-VL-29516 (NICHD-sponsored K12 Award to UCLA Department of Pediatrics).